4-Methoxycinnamic acid attenuates schizophrenia-like behaviors induced by MK-801 in mice. (1st March 2022) - Jeong, Yongwoo; Bae, Ho Jung; Park, Keontae; Bae, Hyo Jeoung; Yang, Xingquan; Cho, Young-jin; Jung, Seo Yun; Jang, Dae Sik; Ryu, Jong Hoon
Abstract: Ethnopharmacological relevance: Scrophularia buergeriana has been used for traditional medicine as an agent for reducing heat in the blood and for nourishing kidney ' Yin '. Therefore, S. buergeriana might be a potential treatment for mental illness, especially schizophrenia, which may be attenuated by supplying kidney Yin and reducing blood heat. In a pilot study, we found that S. buergeriana alleviated sensorimotor gating dysfunction induced by MK-801. Aim of the study: In the present study, we attempted to reveal the active component(s) of S. buergeriana as a candidate for treating sensorimotor gating dysfunction, and we identified 4-methoxycinnamic acid. We explored whether 4-methoxycinnamic acid could affect schizophrenia-like behaviors induced by hypofunction of the glutamatergic neurotransmitter system. Materials and methods: Mice were treated with 4-methoxycinnamic acid (3, 10, or 30 mg/kg, i.g.) under MK-801-induced schizophrenia-like conditions. The effect of 4-methoxycinnamic acid on schizophrenia-like behaviors were explored using several behavioral tasks. We also used Western blotting to investigate which signaling pathway(s) is involved in the pharmacological activities of 4-methoxycinnamic acid. Results: 4-Methoxycinnamic acid ameliorated MK-801-induced prepulse inhibition deficits, social interaction disorders and cognitive impairment by regulating the phosphorylation levels of PI3K, Akt and GSK-3β signaling in the prefrontal cortex. And there were no adverse effects in terms of catalepsy and motor coordination impairments. Conclusion: Collectively, 4-methoxycinnamic acid would be a potential candidate for treating schizophrenia with fewer adverse effects, especially the negative symptoms and cognitive dysfunctions. Graphical abstract: Image 1